A qualitative study into the personal factors influencing secondary school teachers’ motivating styles - Liu, Woon Chia; Kong, Leng Chee; Wang, Chee Keng John; Kee, Ying Hwa; Ng, Betsy; Lam, Karen; Reeve, Johnmarshall (Frontiers in Psychology, 2023)
Background. All teachers aspire to create the most motivating classroom climate for their students. This is because students who are motivated demonstrate superior learning outcomes relative to students who are not motivated. According to the Self-Determination Theory (SDT), when teachers establish an autonomy-supportive climate in their classrooms, their students can benefit in numerous developmentally and educationally important ways.While most teachers have an understanding that autonomy-supportive teaching can benefit their students, many of them are unwilling or unable to carry out autonomy-supportive strategies. This can be explained by the implicit and explicit forces (e.g., teaching philosophies and beliefs, personal experiences) imposed on them by their internal (namely, intrapsychic) and external (namely, social) environments. This paper focuses on the personal factors that influence teachers' adoption and employment of autonomy-supportive instructional behaviours. Method. Following a 10-week intervention programme on implementing six autonomy-supportive instructional behaviours, we interviewed 59 teachers from 17 secondary schools in Singapore on their adoption and employment of the teaching strategies. Their number of years of teaching experience ranged from 1 to 31 years with a mean of 10.8 years of teaching experience, and 62.71% of them were female. Finding. From the interviews, we identified several teacher-related personal factors which we labelled "teaching philosophies and beliefs", "personal experiences", "motivation to teach", "personality", "teachers' mental and emotional states" and "teaching efficacy". Through identifying the personal factors, we hope to raise awareness among the teachers on the inner forces that can foster or frustrate their own expression of autonomy-supportive instructional behaviours. Given the many plausible benefits that can be derived from autonomy-supportive teaching, we hope that the information gained from this qualitative study can path the way for greater willingness and effort in implementing autonomy-supportive teaching in the classrooms.